The Integration of Cambridge Curriculum in Islamic Education at Bilingual Boarding School Surakarta - Woro Yustia Pratiwi; Wachidi; Muh. Nur Rochim Maksum; Nur Farid Khoiruddin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
The implementation of global curricula in Islamic schools faces challenges, as some teachers and students have not yet been able to adapt optimally . This study examines the integration of the Cambridge Curriculum at SMA ABBS Surakarta, focusing on planning, implementation, evaluation, as well as supporting and inhibiting factors. Employing a qualitative field research design with a phenomenological approach, data were collected through in-depth interviews, observations, and documentation. The research subjects included the principal, vice principal for curriculum, teachers, and students. The findings reveal that successful implementation of the Cambridge Curriculum in this Islamic school is supported by three main pillars. First, the readiness of human resources, built through tiered training programs and international certification, with teachers required to have at least CEFR B2 English competency. Second, the adoption of innovative learning methods, particularly student-centered learning, practical activities, and authentic assessments that align with Cambridge International standards. Third, adequate infrastructure that meets international benchmarks, thereby facilitating effective curriculum delivery. The novelty of this study lies in its focus on the application of the Cambridge Curriculum within an Islamic school context, which remains relatively rare in Indonesia. The research contributes to the broader discourse on curriculum globalization by highlighting how Islamic schools can integrate international standards while maintaining their religious identity. Practically, the study implies the need to strengthen teacher competencies, sustain infrastructure support, and develop adaptive learning strategies to ensure broader success in similar institutions.